Genome-wide identification, characterization and expression analyses of two TNFRs in Yesso scallop (Patinopecten yessoensis) provide insight into the disparity of responses to bacterial infections and heat stress in bivalves. (May 2016) - Xing, Qiang; Yu, Qian; Dou, Huaiqian; Wang, Jing; Li, Ruojiao; Ning, Xianhui; Wang, Ruijia; Wang, Shi; Zhang, Lingling; Hu, Xiaoli; Bao, Zhenmin
Abstract: Tumor necrosis factors receptors (TNFRs) comprise a superfamily of proteins characterized by a unique cysteine-rich domain (CRD) and play important roles in diverse physiological and pathological processes in the innate immune system, including inflammation, apoptosis, autoimmunity and organogenesis. Although significant effects of TNFRs on immunity have been reported in most vertebrates as well as some invertebrates, the complete TNFR superfamily has not been systematically characterized in scallops. In this study, two different types of TNFR-like genes, including PyTNFR1 and PyTNFR2 g enes were identified from Yesso scallop ( Patinopecten yessoensis, Jay, 1857) through whole-genome scanning. Phylogenetic and protein structural analyses were carried out to determine the identities and evolutionary relationships of the two genes. The expression profiling of PyTNFRs was performed at different development stages, in healthy adult tissues and in hemocytes after bacterial infection and heat stress. Expression analysis revealed that both PyTNFRs were significantly induced during the acute phase (3 h) after infection with Gram-positive ( Micrococcus luteus ) and Gram-negative ( Vibrio anguillarum ) bacteria, though much more dramatic chronic-phase (24 h) changes were observed after V. anguillarum challenge. For heat stress, only PyTNFR2 displayed significant elevation at 12 h and 24 h, which suggests a functional difference in the two PyTNFRs. Collectively, this study provides novel insight into the PyTNFRs and the specific role and response of TNFR-involved pathways in host immune responses against different bacterial pathogens and heat stress in bivalves. Highlights: Genomic-wide identification of TNFR superfamily members confirms only two TNFRs in Yesso scallop. The two PyTNFRs showed different immune response patterns to G + and G − bacteria. Only PyTNFR2 was involved in heat stress response.